Analysis support for the design process of school buildings - Pereira, Paula Roberta Pizarro (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2018)
This paper presents an analysis procedure to improve school design. The procedure uses design parameters, precedent examples and comparisons for a Brazilian context. A literature review on methods and tools to analyse and evaluate architectural school design projects was undertaken. Three methods were singled out to structure the procedure. Design parameters were selected specifically for the Foundation for Educational Development (Fundação para o Desenvolvimento da Educação - FDE). The FDE manages over 5,000 public (non-private) school buildings in the State of São Paulo, Brazil. The literature on school architecture supplied the precedent examples. The procedure contains a structured design analysis method based on design parameters and comparisons between precedents and local design solutions. Tests on 34 design proposals brought to light important parameters for school design and decision-making was more transparent and efficient. The procedure broadens reflections on multidisciplinary aspects of the contemporary school environment and is seen as a design process tool for various contexts to inspire school architecture with users and learning in mind.